Briefly delayed reinforcement effects on variable‐ratio and yoked‐interval schedule performance. Issue 2 (30th July 2013) - Holtyn, August F.; Lattal, Kennon A.
Abstract Most investigations of briefly delayed reinforcement have involved schedules that arrange a time‐plus‐response requirement. The present experiment examined whether briefly delaying reinforcement on schedules that have a ratio requirement differs from results with schedules that have a time‐plus‐response requirement. Four pigeons responded on a two‐component multiple schedule. One component arranged a variable‐ratio (VR) 50 and the other a variable‐interval (VI) schedule in which the distribution of reinforcers was yoked to the preceding VR schedule. Across a series of conditions, delays were imposed in both schedules. These delays were brief (0.25‐ or 0.5‐s) unsignaled delays and, as control conditions, a 5‐s unsignaled delay and a 0.5‐s delay signaled by a blackout of the chamber. In the yoked‐VI component, the brief unsignaled delay increased response rates in six of nine opportunities and increased the proportion of short interresponse times (IRTs) (<0.4 s) in eight of nine opportunities. In the VR component, the brief unsignaled delay increased response rates and the proportion of short IRTs in only two of nine opportunities. For two of the three pigeons that were exposed to the 5‐s unsignaled delay, response rates and the proportion of short IRTs decreased in both of the components. The 0.5‐s signaled delay did not systematically change response rates nor did it change the distribution of short IRTs relative to the immediate reinforcement condition. The results replicate effects reported with time‐based schedules and extend these observations by showing that changes commonly observed in VI performance with briefly delayed reinforcement are not characteristic of VR responding.